AN ENGLISH RESEARCH JOURNAL WEB PAGE FOR ENGLISH EDUCATION DEPARTMENT OF STKIP PGRI TRENGGALEK - Rika Yulita Hardiyani; Sri Utami Dewi (LinguA-LiterA: Journal of English Language Teaching Learning and Literature, 2020)
This research is to develop An English Research Journal Web Page for English Education Department of STKIP PGRI Trenggalek. The design of this research is R&D education combined with quantitative research methods. Researchers determine the fourth semester of English Education Department STKIP PGRI Trenggalek 2019/2020 academic year as subject. The instruments used in this research were observation, interview, questionnaire, and tests. The data analysis technique of media development uses qualitative and quantitative analysis techniques. This product was developed in five steps of development. The results of the needs analysis score were 2055. Thus, respondents agree that Introduction to Research subjects’ must have a learning media. Further, the results of field-testing score were 2530. It means that the respondents agreed that this research product was very good and was worthy of being used as media in learning Introduction to Research subjects’. Researchers used the paired t-test formula to calculate test results. After receiving the results, the researchers concluded there were an effect on student learning with media development.Furthermore, English Research Journal Web Page has been able to achieve the objective of the research.